Legal provision regulating Intellectual Property in the Republic of Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
Authors of article consider legal regulation of intellectual property in the Republic of Kazakhstan. In particular, the intellectual rights associated with the personality of the author, which include the right to be recognized author of the work , the right to use or permit the use of his true name of the author, pseudonym or without a name (anonymous), the right to disclose or permit the disclosure thereof in any form, including the right to review , as well as the right to protection work, including its name, against any distortion or other derogatory act liable to prejudice his honor or dignity. Under copyright must understand complex legal rules aimed at protecting the results of creative works from copying, performance or distribution without permission; special legally defined rights of authors of works of science, literature and art on the control and use their creations created.
Keywords: intellectual property; copyright; patent; exclusive right